Gender and Computing: not the same old problem - Clegg, Sue; Trayhurn, Deborah (British Educational Research Journal, 2000)
The decline in numbers of women on computing courses in higher education has been the subject of much comment. However, the debate has moved from a 'women and computing' approach to a more sophisticated theorisation of gender. We suggest that computing also requires better theorisation. Computing is most usefully characterised as a concrete not abstract science. Women's contribution to the field is often ignored because they are seen as end-users, not part of the academic mainstream. We report a case study of men and women on applied information technology courses. Using data from in-depth interviews, we found that both men and women were aware of gender in computing practice. However, both men and women expressed intrinsic as well as instrumental reasons for studying and the women were confident in their own abilities. Women brought with them valuable administrative experience of using computer systems. One of the challenges is to conceptualise women's computer skills as real computing and to ask what is wrong with computing rather than what is wrong with women.
Keywords: compétence; compétence informatique; enseignement supérieur; genre; éducation prioritaire